2003
DOI: 10.1108/09578230310489353
|View full text |Cite
|
Sign up to set email alerts
|

Cause maps and school leaders’ tacit knowledge

Abstract: The complexity of the work of school leaders has intensified in recent years. The basic assumption underlying this article is that school leaders should develop a coherent vision of the school to effectively cope with the increased complexity of their work. In order to develop such a coherent vision, integration at a cognitive level is needed. In order to gain insight into both the complexity and integrity of the visions of school leaders, their tacit knowledge is studied using cause maps. More specifically, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…More recently, researchers have focused on mental models and tacit understandings of school leaders in order to understand the knowledge and concepts they use to interpret information and solve problems at hand (Nestor-Baker & Hoy, 2001;Ruff & Shoho, 2005;Wassink, Sleegers, & Imants, 2003). These researchers have paid attention to the specific knowledge structures school leaders construct through the use of generic knowledge and the underlying assumptions used to organize their understanding of new information and repertoires of responses to experiences.…”
Section: Sense-making and School Leadershipmentioning
confidence: 98%
See 2 more Smart Citations
“…More recently, researchers have focused on mental models and tacit understandings of school leaders in order to understand the knowledge and concepts they use to interpret information and solve problems at hand (Nestor-Baker & Hoy, 2001;Ruff & Shoho, 2005;Wassink, Sleegers, & Imants, 2003). These researchers have paid attention to the specific knowledge structures school leaders construct through the use of generic knowledge and the underlying assumptions used to organize their understanding of new information and repertoires of responses to experiences.…”
Section: Sense-making and School Leadershipmentioning
confidence: 98%
“…In contrast to research on problem solving and expertise, these studies do not focus on discrete cognitive categories and relatively static characteristics of problem solving only, but also on the dynamics of school leaders' frames of references as developed through their previous experiences and cycles of events, ideas, roles, etc. The results of the few studies conducted demonstrated the complex nature of the mental models of school leaders and the differing levels of integration and variation regarding the content of the models (Wassink, Sleegers, & Imants, 2003).…”
Section: Sense-making and School Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…This element is later elaborated in which could be called the cognitive perspective on educational leadership (Hallinger, Leithwood, & Murphy, 1993;Leithwood, 1995). The concepts of higher order thinking and vision have been conceptualized further, for instance in research into effective administrative problem-solving, based on cognitive perspectives on leadership Wassink, Sleegers, & Imants, 2003). In this research, vision is related to expertise on problem-solving and decisionmaking, and the results show that principals who engage in higher order thinking are better able to apply relevant knowledge about their school and the school's curriculum to solving problems.…”
Section: Theoretical Framework: Principals' Impact On Processes and Omentioning
confidence: 99%
“…So far, literature on the cognitive perspective of educational administration has mainly focused on principals' thinking about practical problems and how to solve them, and summarized findings on how expertise is developed and on how novices and experts display their knowledge in a school setting (Hallinger, Leithwood, & Murphy, 1993;Leithwood & Steinbach, 1992Stager & Leithwood, 1989). More recent studies (Wassink, Sleegers, & Imants, 2003;Krüger, Witziers, & Sleegers, 2007) have analyzed the impact of the principals' vision and tacit knowledge on their activities. These activities can play a salient role in shaping the school climate.…”
Section: Role Conceptions and Role Priorities Leadership Behavior Amentioning
confidence: 99%